A Remark About Hyperbolic Equations with Log-Lipschitz Coefficients (Journal of Partial Differential Equations, 1997)
We prove the well-posedness of the Cauchy problem for strictly hyperbolic equations and systems with Log-Lipschitz coefficients in the time variable.
Keywords: Strictly hyperbolic equations; non regular coefficients